Actions of some analogues of 5-hydroxytryptamine on the isolated rat uterus and the rat fundus strip preparations - Barlow, R. B. (1959)
The search for substances which antagonize 5-hydroxytryptamine, and for those which act like it, has been extended to cover 5-substituted indoles which are analogues of 5-hydroxytryptamine, rather than analogues of tryptamine like the compounds previously studied by us. The isolated rat uterus and rat fundus strip preparations have been used to determine activity. The relationships between structure and activity of the compounds studied were not the same on the two preparations nor were they the same from one homologous series to another. These differences may be partly explained by the presence of amine oxidase in the rat fundus, as Vane (1959) has suggested, and by supposing that it is absent from the rat uterus. None of the compounds had marked antagonist activity. The most active antagonist on the rat uterus was 3-(2-aminopropyl)-5-benzyloxyindole, but this was less potent than 5-benzyloxygramine. On the rat fundus strip, however, the only antagonist, 5-benzyloxy-3-(2-dimethylaminoethyl)indole, was more active than 5-benzyloxygramine. On both preparations the most active stimulant was 3-(2-aminopropyl)-5-benzyloxyindole, which was about half as potent as 5-hydroxytryptamine. The next most active were 3-(2-aminopropyl)-5-methoxyindole and bufotenine.